Internalization of Typical Curriculum Religious Values as A Strengthening of The Character of MTs Mathla'ul Anwar Students Telukambulu, Karawang District - Hisan, Ira Hoirot; Suharyat, Yayat; Alam, Dede Rubai Misbahul (Proceeding International Conference on Education, 2023)
Internalising religious values in a typical curriculum is important in strengthening student character. This study aims to analyse the process of internalising religious values in a typical curriculum and its impact on strengthening students' character at MTs Mathla'ul Anwar. Data collection techniques include class observations, interviews, and analysis of curriculum documents. Data analysis was carried out using a qualitative approach. Observational data, interviews, and document analysis were studied thematically to identify internalisation patterns of religious values in a typical curriculum and their impact on strengthening student character. The sample of this research is students. The results of the study show that the process of internalising religious values in a typical curriculum has a significant impact on strengthening student character. Students experience changes in attitudes, behavior, and a deeper understanding of religious values. They can apply these values in everyday life, such as being kind, honest, tolerant and responsible. The implication of this research is the importance of developing a distinctive curriculum that focuses on internalising religious values to strengthen student character.